INCIDENCE OF DENTINAL MICROCRACKS AFTER ROOT CANAL PREPARATION WITH TWO RECIPROCATING SYSTEMS: A STEREOMICROSCOPIC STUDY - Irina Tsenova; Radosveta Vassilev; Emilia Karova (Peytchinski Publishing, 2018)
Purpose: The objective of the present study was to evaluate the incidence of microcracks after root canal preparation with two reciprocating systems. Materials and methods: Thirty - six freshly extracted mandibular incisors were selected for this in vitro study. The samples were allocated in three groups (n=12): negative control, Reciproc, WaveOne Gold. Roots in the control group were left unprepared. Reciproc R25 and WaveOne Gold Primary files were used in the other groups. After shaping of the root canals teeth were horizontally sectioned at 3, 6, 9 mm from the apex and the presence of dentinal defects were registered. These data were analyzed statistically by Fisher's exact and chi-square tests (p < 0.05). Results: No defects were observed in the control group. All instruments caused dentinal microcracks with no statistically significant differences between the two systems. Defects in the apical region in both experimental groups differed statistically from those in the coronal portion of the roots. Conclusions: WaveOne Gold and Reciproc systems performed equally and resulted in dentinal defect formation regardless of their alloy type, taper and cross-section.